Gaya Hidup dengan Kejadian Hipertensi pada Lansia - Manah, Siti Nur; Rahmawati, Teti (Universitas Baiturrahim, 2024)
Elderly (Elderly) are a group of 60 years and over who experience various physiological changes that can affect the lifestyle of the elderly to become less healthy which includes physical activity, eating patterns, resting habits, and smoking habits which can trigger various health problems, including hypertension. This study aims to identify the relationship between lifestyle and the incidence of hypertension in the elderly at the Sukaluyu Health Center. This research is a quantitative study using the correlation method with a cross sectional approach. The study population was elderly aged 60-90 years who came to the Sukaluyu Health Center as many as 153 people with a sample of 122 people who were determined using the Frank Lynch formula corrected by the drop out formula. Data collection was carried out using a questionnaire. The results of the univariate analysis showed that most of the elderly belonged to the elderly category (60-74 years) as much as 86.9%, were female (85%), had primary school education (66.4%), and did not have a job (58, 2%). Bivariate analysis using the Chi-Square test with a 95% confidence level (p value = 0.05) showed no relationship between lifestyle and the incidence of hypertension in the elderly at the Sukaluyu Health Center with a p value of 0.130. The study recommends that health workers improve the provision of education to the elderly and their families about appropriate lifestyles to prevent hypertension.